A pilot study of the effects of meditation on regional brain metabolism in distressed dementia caregivers. (October 2012) - Pomykala, Kelsey L; Silverman, Daniel HS; Geist, Cheri L; Voege, Patricia; Siddarth, Prabha; Nazarian, Nora; Cyr, Natalie M St; Khalsa, Dharma S; Lavretsky, Helen
Aims: Caregiver distress can affect mood and cognition. Meditation can be used to reduce stress. This pilot study explored whether yogic meditation could change regional cerebral metabolism in distressed caregivers.Methods: Nine dementia caregivers were randomized to undergo meditation training compared with relaxation for 12 min per day for 8 weeks. Caregivers received neuropsychiatric assessments and brain FDG-PET scans at baseline and postintervention.Results: The groups did not differ on measures of mood, mental and physical health, and burden at baseline and follow-up. When comparing the regional cerebral metabolism between groups, significant differences over time were found in the bilateral cerebellum (p < 0.0005), right inferior lateral anterior temporal (p < 0.0005), right inferior frontal (p = 0.001), left superior frontal (p = 0.001), left associative visual (p = 0.002) and right posterior cingulate (p = 0.002) cortices.Conclusion: Meditation practice in distressed caregivers resulted in different patterns of regional cerebral metabolism from relaxation. These pilot results should be replicated in a larger study.